Ways of Forming Words in Present-Day English - Xaydarova Muattar Iskandarovna (International Journal on Integrated Education, 2022)
The article illustrates the point when in two languages we find no trace of the exchange of loanwords one way or other we are safe to infer that the two nations have had nothing to do with each other, but if they have been in contact, the number of the loan– words and still more the quality of the loanwords, if rightly interpreted, will inform us of their reciprocal relations, they will show us which of them has been the more fertile in ideas and on what domains of human activity each has been superior of the other.